Income and greenhouse gas (GHG) emission trade-offs on smallholder farms at two sites in northern Nigeria - Ayinde, T.; Nicholson, C.F.; Ahmed, B.; Ayantunde, Augustine A.; Akinola, M.; Yusuf, O. (2020)
This study analyses the trade-offs between welfare (measured by income) and greenhouse gas (GHG) emissions using a farm-level optimisation model that incorporates the predominant cereal (sorghum), legumes (groundnut, soybeans), livestock (cattle, goats and sheep) and trees (locust bean, camel’s foot) representative of production systems at two contrasting sites in northern Nigeria. The optimisation model maximises the value of total farm production, subject to constraints on GHG reductions of 10%, 25% and the maximum reductions that allow households to meet minimum consumption requirements. Substantive reductions in livestock and legume production would be required to achieve the maximum possible reductions from current emissions and would reduce household income by 22% and 44%, respectively. Under current production practices, reductions in GHG emissions reduce household income, which suggests the need for further research on productivity-enhancing technologies that could both enhance income and reduce GHG emissions in these production contexts.